The Influence of Social Behavior to The Emergence Residential Segregation in Sleman Regency D.I Yogyakarta - Fitra, Helmia Adita; Pradoto, Wisnu (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
As a peri-urban area of Yogyakarta City, Sleman Regency has become transition zone in which the transitions of land use and socio-economic are occurred. Those transitions have resulted in diversed socio-economic background of people who live in Sleman Regency. In the context of urban development, if the diversed socio-economic factor is unmanaged, the diversed socio-economic factor may become a vulnerable factor related to discrimination of minority group resulting lack of public participation due to lack of coordination among local people and migrants. Discrimination or exclusion to a certain group or community in residential area is usually called as residential segregation. In terms of study, researcher is going to reveal about â€œis there any influence of social behavior to residential segregation? If so, then how strong the influence of social behavior to residential segregation?â€. Analysis of influence of social behavior is conducted to socio economic factor. This study conducts a quantitative method. Referring to the analysis result, there are segregations which are emerged in research area mainly segregation by income and segregation by education level. Both of segregations show that socio-economic factors have influenced the emergence of segregation especially for the variable of income level. The variable of income level has been proven influencing the segregation by income level about 20,8% and segregation by education level about 19%. Some areas which is included into weak segregation are Ngaglik, Depok, Berbah, Gamping and Ngemplak while some areas which is included into strong segregation are Godean, Kalasan, Ngemplak and Sleman.